Water-mediated protein-DNA interactions: the relationship of thermodynamics to structural detail. - Morton, C. J. (Cold Spring Harbor Laboratory Press, 1996)
The elucidation of a relationship between the thermodynamic parameters and the structural changes accompanying biomolecular interactions could lead to predictive algorithms. For example, based on some knowledge of the structure of a target molecule the affinities of ligands could be determined with obvious implications for the pharmaceutical industry. In attempting to relate the thermodynamic and structural changes on formation of a protein-DNA complex, the correlation between change in heat capacity and burial of surface area has proved successful. However, this correlation appears to break down when water molecules are included in the binding interface. Here we present data that support the hypothesis that bound water molecules have to be considered as contributing to the change in heat capacity and could, thus, be used in ligand design.